Method for reducing reflectivity during laser cladding of copper alloy substrate

By preparing a nickel-based alloy transition layer on the copper alloy matrix, the problem of high reflectivity during laser cladding is solved, and high-efficiency and low-energy metallurgical connection is achieved, reducing the risk of equipment damage.

CN116555757BActive Publication Date: 2025-03-18UNIV OF JINAN

Patent Information

Application Number
CN202310648023.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-03-18
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

The reflectivity of the copper alloy matrix is ​​high during laser cladding, resulting in light intensity reflection damage to equipment, etc. The prior art reduces the reflectivity by electroplating, but there are problems such as high power consumption, high cost and waste of plating.

Method used

The nickel-based alloy transition layer is prepared by woven, glue coating, spreading nickel-based alloy powder and drying, so as to reduce the reflectivity of the copper alloy matrix and form metallurgical connections during laser cladding.

Benefits of technology

It effectively reduces the reflectivity of the copper alloy matrix, improves the efficiency of laser cladding and the firmness of metallurgical connections, and reduces overall energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116555757B_ABST
    Figure CN116555757B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for reducing reflectivity during laser cladding of a copper alloy substrate, the method comprising the following steps: 1) roughening a target surface of a given copper alloy workpiece; 2) brushing volatile glue on the target surface after cleaning the target surface; 3) spreading nickel-based alloy powder on the target surface to completely cover the target surface; 4) shaking off the unattached nickel-based alloy powder and drying to form a transition layer; 5) preparing a target coating on the transition layer. The method according to the present invention has relatively low power consumption and relatively high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for reducing reflectivity during laser cladding of a copper alloy substrate. Background Art

[0002] Pure copper and its alloys are metal materials with high reflectivity. In specific industrial applications, the application range of copper alloys is much higher than that of pure copper. For example, brass, bronze, etc. are actually copper alloys. However, whether it is pure copper or copper alloy, when it has a clean surface and the surface accuracy is higher than IT7, its surface reflectivity is usually greater than or equal to 40%. It is well known that the laser cladding process requires that under the thermal effect of the laser, for example, a molten state is generated between the coating and the copper alloy substrate. In other words, the part absorbed by the coating should be enough to melt the copper alloy surface, so the reflected part can almost cause the copper alloy surface to melt. The light intensity of the reflected part is also large enough to easily damage the objects and equipment illuminated by the reflected light.

[0003] In view of this, for example, Chinese patent document CN107868955A proposes a method for preparing a laser-strengthened coating on the surface of a copper crystallizer (hereinafter referred to as the workpiece). In order to reduce the laser reflection intensity on the surface of the workpiece during coating preparation, an intermediate transition layer is first prepared on the surface of the workpiece before preparing the coating. The specific method is to electroplate or electrobrush-plate a pure nickel layer or a nickel-based alloy layer on the surface of the workpiece after cleaning the surface of the workpiece, and then remelt the electroplated layer by laser cladding to ensure that the electroplated layer is melted through so that a reliable metallurgical connection is formed between the laser remelted layer and the copper matrix of the crystallizer.

[0004] The bonding strength of the electroplating layer is relatively low, so the Chinese patent document CN107868955A proposes to use laser remelting technology to create a metallurgical connection between the electroplating layer and the workpiece surface. It should be noted that the electroplating solution required for the preparation of the electroplating layer is not a simple electroplating solution containing metal ions of the electroplating layer, but also contains a large number of other types of metal ions or additives, many of which are environmental pollutants, and the electroplating process is generally long. In addition, for workpieces, not all surfaces need to be electroplated. For example, copper shells usually only need to be coated on their outer surfaces. Electroplating requires immersing the workpiece in the electroplating solution, which will inevitably lead to waste of coating and control problems of workpiece size (other surfaces that do not require coating).

[0005] In addition, the power consumption and cost of electroplating itself are relatively high. Generally, additional cleaning and drying are required after electroplating, and the overall working hours are relatively long. Summary of the invention

[0006] The object of the present invention is to provide a method for reducing reflectivity during laser cladding of a copper alloy substrate with relatively low power consumption and relatively high efficiency.

[0007] In an embodiment of the present invention, a method for reducing reflectivity during laser cladding of a copper alloy substrate is provided, the method comprising the following steps:

[0008] 1) Roughening the target surface of a given copper alloy workpiece;

[0009] 2) After cleaning the target surface, apply volatile glue on the target surface;

[0010] 3) Spreading nickel-based alloy powder on the target surface to completely cover the target surface;

[0011] 4) Shake off the unattached nickel-based alloy powder and dry it to form a transition layer;

[0012] 5) Preparing a target coating on the transition layer.

[0013] Optionally, the nickel-based alloy is Ni25 or self-fluxing nickel-based alloy powder.

[0014] Optionally, the self-fluxing nickel-based alloy powder is Ni-B-Si alloy powder.

[0015] Optionally, the Ni25 powder is a spherical alloy powder with a particle size of 150-300 meshes.

[0016] Optionally, the composition of Ni25 in mass percentage is: C0.5%, Cr15%, Si2.5%, B1.8, Al0.5%, Fe7%, and the balance is Ni.

[0017] Optionally, in step 4), before shaking off the unattached nickel-based alloy powder, the target surface needs to be left to stand for at least 2 minutes after the nickel-based alloy powder is completely covered.

[0018] Optionally, the method for roughening the target surface is to use 200-grit sandpaper to roughen the target surface.

[0019] Optionally, the volatile glue is prepared by mixing vinyl alcohol and water in a ratio of 10 g:20 ml, wherein the water is deionized water.

[0020] Optionally, in step 4), the drying method is to place the copper alloy workpiece after shaking off the unattached nickel-based alloy powder into a drying oven, with a drying temperature of 200° C. and a drying time of 120 min.

[0021] Optionally, after step 4) drying, the copper alloy workpiece is taken out and naturally cooled to room temperature.

[0022] In an embodiment of the present invention, the target surface of the copper alloy workpiece is first roughened, at which time the reflectivity of the target surface itself will decrease, and it will also help other materials to adhere. Then, volatile glue is applied to the target surface, nickel-based alloy powder is sprinkled on the volatile glue, excess nickel-based alloy powder is shaken off, and a relatively stable transition layer is obtained by drying, so that the thickness of the obtained transition layer is relatively uniform. Then, the target coating is prepared on the transition layer. In this process, the efficiency is relatively high, and when the target coating is prepared by cladding, the transition layer is also clad, and a metallurgical connection is formed at the same time, which is relatively efficient and reduces energy consumption as a whole. At the same time, the metallurgical connection has better bonding firmness than the electroplating layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The figure is a flow chart of a method for preparing a transition layer in one embodiment.

[0024] Figure 2 Schematic diagram of the transition layer cladding structure in one embodiment.

[0025] Figure 3 This is an electron microscope image of a coating prepared on a copper alloy substrate in an experimental example.

[0026] Figure 4 The following are comparison diagrams of the wear scar morphology of the substrate and the coating in an experimental example, where Figure a is an electron microscope photograph of the substrate wear scar, and Figure b is an electron microscope photograph of the coating wear scar.

[0027] In the figure: 1. Copper alloy substrate, 2. Ni25 alloy powder, 3. Transition layer. Implementation

[0028] The color of nickel-based alloy is darker than other alloys. In other words, it also indicates that its reflectivity is relatively low under the same precision state. At the same time, the layer formed by spreading nickel-based alloy powder does not have a smooth surface, but reflects light in a diffuse reflection characteristic. In the embodiment of the present invention, it is equivalent to preparing a coating with nickel-based alloy powder as the base.

[0029] It can be seen that after the coating is prepared, the excess nickel-based alloy powder is easy to remove because it is only attached by the volatile glue.

[0030] The embodiment of the present invention focuses on reducing the reflectivity of laser cladding when preparing the copper alloy substrate coating. The mechanism can be found in Chinese patent document CN107868955A, which will not be described in detail here. However, it should be noted that the embodiment of the present invention focuses on how to prepare the intermediate transition layer, such as Figure 2 The transition layer 3 is shown in the figure, and how to prepare the coating is only briefly described, and those skilled in the art should have a clear understanding.

[0031] As for the transition layer 3, it only needs to be able to effectively reduce the reflectivity of the copper-based alloy surface. Therefore, the transition layer 3 can be very thin. In other words, it only needs to be able to cover the target surface of the copper-based alloy substrate.

[0032] Correspondingly, under the condition of adding a relatively thin transition layer 3 , the influence on laser cladding is relatively low, and the coating and the transition layer 3 can be laser clad as a whole.

[0033] The following describes the basic steps of a method for reducing reflectivity during laser cladding of a copper alloy substrate. The basic steps include four basic steps: roughening, gluing, powder coating, and drying. Each step can assist other steps. For example, roughening often requires simple cleaning, which can be done by brushing off the particles formed by roughening or cleaning in other ways. If water washing is used, the water stains need to be cleaned and air-dried in a preferred embodiment. To this end, each basic step is explained one by one below.

[0034] First of all, it should be known that the surface for preparing the coating is not necessarily the entire surface of the copper alloy workpiece, but usually a part of the outer surface of the copper alloy workpiece. The layer that needs to be coated is recorded as the coating surface. The surface formed by the transition layer is recorded as the target surface, which can be slightly larger than the coating surface, for example, each side is wider than 3D~10D, where D is the spot diameter during laser cladding. For example, if the spot diameter is 1mm, the target surface is 3~10mm wider on each side relative to the coating surface.

[0035] Regarding the roughening step, mechanical roughening is preferably used, and chemical etching can also be used. Among them, chemical etching is not a preferred method because chemical etching is relatively less environmentally friendly.

[0036] Mechanical roughening includes machine roughening and manual roughening, such as roughening with a belt machine or manual roughening with sandpaper. Technicians in this field can choose according to the batch size. For example, when the batch is relatively small or samples are produced, manual roughening can be preferably used. If the batch is relatively large, mechanical roughening is preferably used.

[0037] Whether using a belt sander or sandpaper, the corresponding sand particle size can be consistent, for example, 200 mesh. Since it is polishing, the sand particle size should not be too small, so it should not be less than 150 mesh, but it should not be too large, otherwise it will damage the target surface. Therefore, the sand particle size should not be greater than 300 mesh.

[0038] The main purpose of roughening is to make the target surface rough, thereby improving the adhesion performance of nickel-based alloy powder on the target surface.

[0039] The next step is cleaning, which mainly removes particles attached to the target surface, as mentioned above. To ensure thorough cleaning, you can first perform mechanical cleaning after roughening, such as wiping with a towel, and then use anhydrous ethanol for cleaning. Anhydrous ethanol can effectively remove organic matter on the target surface and prevent, for example, grease from affecting the bonding strength of the coating.

[0040] For example, anhydrous ethanol has better volatility and can be evaporated in a shorter time. If deionized water is used, it is preferably further dried by, for example, air drying to improve the efficiency of the process.

[0041] After cleaning the target surface, apply volatile glue on the target surface; for example, glue formed by mixing polyvinyl alcohol powder and water, the ratio is 10g:20ml, deionized water is selected, polyvinyl alcohol powder is added into the water, and stirred evenly.

[0042] Then, the volatile glue is applied on the target surface by brushing. The thickness of the formed glue layer is very thin. From the perspective of suitability, the transition layer 3 does not need to be too thick. It only needs to have a certain shielding property, that is, it can shield the copper alloy surface.

[0043] Then the powder is spread by sprinkling powder. The powder is naturally adhered to the volatile glue. The adhesion amount is affected by the thickness of the glue layer and will not be too much. Generally, a powder layer with a thickness of 0.5~1mm is formed. Obviously, the powder layer is a nickel-based alloy powder layer.

[0044] Based on the evenly applied volatile glue, the spread nickel-based alloy powder can completely cover the target surface; in order to ensure complete coverage of the target surface, the spread amount should be excessive. Under this condition, after spreading, the excess nickel-based alloy powder is shaken off to reduce the amount of free nickel-based alloy powder, so that the transition layer 3 before cladding is relatively stable, thereby facilitating the formation of the coating.

[0045] Regarding nickel-based alloy powder, low eutectic nickel-based alloy is preferably used. Low eutectic nickel-based alloy is a standard term used to define nickel-based alloy powder formed by adding appropriate amounts of B and Si to nickel alloy powder. There are relatively many types, such as Ni-B-Si alloy powder, Ni-Cr-B-Si alloy powder, Ni-Cr-B-Si-Mo, Ni-Cr-B-Si-Mo-Cu, high molybdenum nickel-based self-fluxing alloy powder, high chromium molybdenum nickel-based self-fluxing alloy powder, Ni-Cr-WC-based self-fluxing alloy powder, high copper self-fluxing alloy powder, tungsten carbide dispersion type nickel-based self-fluxing alloy powder, etc.

[0046] More preferably, the nickel-based alloy powder is Ni-B-Si alloy powder.

[0047] Correspondingly, the low eutectic nickel-based alloy has a low melting point, which is conducive to the formation of metallurgical bonding between the transition layer 3 and the copper alloy substrate 1, as well as the coating.

[0048] In some embodiments, the nickel-based alloy powder is preferably nickel 25 alloy powder. The composition of Ni25 in mass percentage is: C0.5%, Cr15%, Si2.5%, B1.8, Al0.5%, Fe7%, and the balance is Ni.

[0049] In order to make the Ni25 alloy powder 2 relatively tightly bonded, before shaking off the free nickel-based alloy powder, the target surface needs to be completely covered with the nickel-based alloy powder and left to stand for at least 2 minutes, so that the Ni25 alloy powder 2 and the volatile glue are relatively tightly bonded.

[0050] It is obvious that the volatile glue should be basically completely volatilized when preparing the coating. Therefore, before preparing the coating, most of the volatile glue is volatilized by forced drying. The remaining volatile glue is tightly combined with the nickel-based alloy powder to form a transition layer 3.

[0051] The main method of forced drying to volatilize the volatile glue is to shake off the unattached nickel-based alloy powder and place the copper alloy workpiece into a drying oven. The drying temperature is 200°C and the drying time is 120 minutes.

[0052] Since the drying temperature is not high, natural cooling is preferably used for cooling after forced drying.

[0053] In order to verify the coating quality after adding the transition layer 3, the Ni60+WC coating is taken as an example for explanation. In the selected Ni60+WC coating, the mass fraction ratio of Ni60 to WC is 4:1.

[0054] The selected laser operating parameters are: laser power 1400W, powder feeding rate 6.5L / min, overlap rate 40, spot diameter 1mm, and laser scanning speed 300mm / min.

[0055] The nickel-based alloy powder of the transition layer is Ni25, and the volatile glue used is a mixture of polyvinyl alcohol powder and water in a ratio of 10g:20ml.

[0056] The thickness of the powder layer is 0.7 mm.

[0057] Figure 3 This is an electron microscope photograph of the cross section of the prepared coating. It can be seen in the figure that although there is a transition layer (the middle layer in the figure, the bottom layer in the figure is the copper alloy base layer, and the top layer is the coating), it can be seen that a metallurgical bond has been formed and there are no obvious pores or cracks.

[0058] Figure 4 The friction and wear test of the coating prepared by taking Ni60+WC coating as an example, using GCr15 as the wear part, loading force 50N, frequency 5Hz, friction and wear time 1h, to prove the performance of the coating. The morphology after friction and wear was observed under a scanning electron microscope. It can be observed that the friction and wear width of the substrate is much larger than that of the coating, and the substrate forms a large area of ​​metal extrusion accumulation and peeling, and its main friction and wear mechanism is fatigue wear; while there are only a few peeling and shallow furrows on the surface of the coating, and its wear mechanism is fatigue wear and abrasive wear. Comparison between the two shows that the friction and wear performance of the coating is higher than that of the substrate. At the same time, the coating meets the strength of metallurgical connection, and can cause the friction and wear conditions of substrate peeling, but does not cause the peeling of the coating. In other words, under the condition of adding a transition layer, the coating and the substrate still have the ability to combine metallurgically.

Claims

1. A method for reducing reflectivity during laser cladding of a copper alloy substrate, characterized in that: The method comprises the following steps: 1) Roughening the target surface of a given copper alloy workpiece; 2) After cleaning the target surface, apply volatile glue on the target surface; 3) Spreading nickel-based alloy powder on the target surface to completely cover the target surface; 4) Shake off the unattached nickel-based alloy powder and dry it to form a transition layer; 5) preparing a target coating on the transition layer; The method of roughening the target surface is to use 200-grit sandpaper to roughen the target surface; The nickel-based alloy is Ni25 or self-fluxing nickel-based alloy powder; The self-fluxing nickel-based alloy powder is Ni-B-Si alloy powder; The composition of Ni25 in mass percentage is: C0.5%, Cr15%, Si2.5%, B1.8, Al0.5%, Fe7%, and the balance is Ni; In step 4), before shaking off the unattached nickel-based alloy powder, the target surface must be completely covered with nickel-based alloy powder and left to stand for at least 2 minutes; The drying method in step 4) is to place the copper alloy workpiece after shaking off the unattached nickel-based alloy powder into a drying oven at a drying temperature of 200° C. for a drying time of 120 minutes.

2. The method according to claim 1, characterized in that The Ni25 powder is a spherical alloy powder with a particle size of 150-300 meshes.

3. The method according to claim 1, characterized in that The volatile glue is prepared by mixing vinyl alcohol and water in a ratio of 10g:20ml, wherein the water is deionized water.

4. The method according to claim 1, characterized in that: Step 4) After drying, take out the copper alloy workpiece and allow it to cool naturally to room temperature.

Citation Information

Patent Citations

  • Preparation method of surface laser-strengthened coating for copper crystallizer

    CN107868955A

Cited By

  • High-strength multifunctional multilevel structure coating and preparation method

    CN117821968A

  • High-strength multifunctional multistage structure coating and preparation method

    CN117821968B